Pore-structure characterisation of tectonically deformed shales: a case study of Wufeng-Longmaxi Formation in western Hunan Province, southern China. Issue 7 (3rd October 2019) - Li, Z.; Jiang, Z.; Liang, Z.; Yu, H.; Yang, Y.
Abstract: The impacts of tectonic deformation on pore structure of the Wufeng-Longmaxi shales in southern China were studied on tectonically deformed shales. Core description, thin-section observation, total organic carbon, X-ray diffraction, low-pressure gas (N2 and CO2 ) adsorption, mercury intrusion capillary pressure and field emission-scanning electron microscopy experiments were performed. The undeformed shale (UDS), brittle deformed shale (BDS) and ductile deformed shale (DDS) can be sorted based on the variability of original texture, fabric and structure properties of the shale samples. In addition, shale samples with different deformation mechanisms have various pore-structure characteristics. Organic matter pores and interparticle pores in clay minerals are the dominant pore types in the selected shale samples. The BDS sample has a greater proportion of macropores (or micro-fractures), indicating brittle tectonic deformation has a significant effect on the development of macropores in shales. In contrast, the DDS sample has more micropores than the UDS and BDS samples, suggesting ductile tectonic deformation may damage larger pores owing to the compression by complex tectonic stress.